1980
DOI: 10.1254/jjp.30.187
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological study on sympathetic inhibition of the urinary bladder in dogs.

Abstract: Abstract-The sympathetic inhibitory mechanism in dog urinary bladder was studied. The bladder contractions induced by electrical stimulation of the pelvic nerve both proximal and distal to the pelvic plexus and by intraarterial administration of tetra methylammonium (TMA) were inhibited by stimulation of the hypogastric nerve and intraarterial injection of catecholamines.The inhibition by hypogastric nerve stimu lation was more potent at the low frequency of pelvic nerve stimulation than at the high frequency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…With regard to the sympathetic nerve innervation of the rat bladder, an excitatory a-receptor (2) and an inhibitory 19-receptor (2, 4) have been reported on the detrusor muscle, and it has also been reported that reserpine induces hyperreflexia (5). In cat and dog bladder (16,17), sympathetic inhibition is mediated by an a-receptor in the pelvic ganglia and by a a-receptor on the detrusor muscle. In the present study, phentolamine (5 mg/kg, i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the sympathetic nerve innervation of the rat bladder, an excitatory a-receptor (2) and an inhibitory 19-receptor (2, 4) have been reported on the detrusor muscle, and it has also been reported that reserpine induces hyperreflexia (5). In cat and dog bladder (16,17), sympathetic inhibition is mediated by an a-receptor in the pelvic ganglia and by a a-receptor on the detrusor muscle. In the present study, phentolamine (5 mg/kg, i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation of sympathetic nerves (either the hypogastric nerve or the lumbar sympathetic chain) inhibits transmission in bladder ganglia of the cat (169,170,362,549) rabbit (649), guinea pig (3,423), and dog (489) but not in the rat (510, 606) or mouse (522). …”
Section: Peripheral Nervous Systemmentioning
confidence: 99%
“…Several species and experimental approaches have been used to investigate the physiology and pathophysiology of the urogenital tract. Most investigations have been performed under anaesthesia in rats [ 1], rabbits [ 2], cats [ 3, 4] or dogs [ 5, 16–18]. In conscious rabbits, vesical function [ 19] or AP have been explored [ 20] in separate experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, the micturition reflex [ 3] and bladder motility during filling [ 4] have also been studied in detail. In dogs, the sympathetic inhibitory mechanism of urinary bladder contraction induced by electrical stimulation of the pelvic nerve was studied [ 5].…”
Section: Introductionmentioning
confidence: 99%